2016
DOI: 10.2174/1872212110666160518130259
|View full text |Cite
|
Sign up to set email alerts
|

Status and Prospect of the Evaluation of the Global Wave Energy Resource

Abstract: Background: With the increasingly serious energy and environmental crises and shortages of conventional energy such as coal and oil, humans have been focusing on new energy sources, especially the abundant wave energy resource. Previous researchers have made great contributions to the design of wave energy converters and have also applied for many patents. However, advanced comprehensive wave energy evaluation and application systems are still scarce, which results in the primitive state of wave energy evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Also, the overall capture efficiency and the WEC's lifespan had a relevant impact on the system's stability [52][53][54][55]. The utilization factor of wave energy was closely related with the significant wave height [53,56], whereas energy quality was determined by the energy level occurrence [57]. Ultimately, Zheng et al suggested several improvement opportunities for the wave energy prediction capacity, such as the incorporation of climate prediction methods and the application of numerical simulation methods and swell propagation characteristics.…”
Section: Long-term Forecastingmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the overall capture efficiency and the WEC's lifespan had a relevant impact on the system's stability [52][53][54][55]. The utilization factor of wave energy was closely related with the significant wave height [53,56], whereas energy quality was determined by the energy level occurrence [57]. Ultimately, Zheng et al suggested several improvement opportunities for the wave energy prediction capacity, such as the incorporation of climate prediction methods and the application of numerical simulation methods and swell propagation characteristics.…”
Section: Long-term Forecastingmentioning
confidence: 99%
“…The authors concluded that long-term climate trends and predictability of wave energy still remained scarce. Also, the overall capture efficiency and the WEC's lifespan had a relevant impact on the system's stability [52][53][54][55]. The utilization factor of wave energy was closely related with the significant wave height [53,56], whereas energy quality was determined by the energy level occurrence [57].…”
Section: Long-term Forecastingmentioning
confidence: 99%
“…The wave energy potential of a region depends on height of the waves which again depend on speed, duration, and fetch of the wind flowing in that region. 14,15,16 According to Sisco et al, 17 changes in climatic trend have impacted the normal pattern of climatic parameters such as wind speed and its duration in many parts of the world. As a result, potential of wave energy has also changed on those locations.…”
Section: Chakraborty Et Almentioning
confidence: 99%
“…However, as with the other alternative sources of energy, variations in regular climatic pattern due to the global warming affect the wave energy potential and average wave power level of a region. The wave energy potential of a region depends on height of the waves which again depend on speed, duration, and fetch of the wind flowing in that region . According to Sisco et al, changes in climatic trend have impacted the normal pattern of climatic parameters such as wind speed and its duration in many parts of the world.…”
Section: Introductionmentioning
confidence: 99%
“…Abundant and nonpollution wave energy has become a particular area of interest for the developed countries. Understanding the characteristics of wave energy resources is very important for the utilization of wave energy program [8], such as wave power generation.…”
Section: Introductionmentioning
confidence: 99%